Prototype for Forest Fire Early Detection System Using the MQTT Method - Simanjuntak, Frisca Tryandayani; Sani, Abdullah; Maulidiah, Hana Mutialif; Puspita, Widya Rika; Budiana, Budiana (Politeknik Negeri Batam, 2024)
The case of forest fires in Batam is one of the natural disasters that often occurs both caused by nature and human error. These forest fires certainly damage forest ecosystems. The condition of the vast forest makes it difficult to monitor the condition of the forest to find the location of the fire. In this study, the authors designed a forest fire early detection system using the concept of Wireless Sensor Network. The system is designed using the MQTT protocol in its data transmission communications. MQTT is a communication protocol that uses the concept of publish-subscribe. Fire information sent by telegram. It is hoped that with this research, it will be able to detect early fires that occur in the forest and be able to become an initial concept for further development. From the test results, it was found that the MQTT protocol sends data well, with subscribers using QoS 0 services having an average delay of 0.050 s, an average throughput of 31355 bps and packet loss of 0%. Subscribers who use QoS 1 services have an average delay of 0.064 s, an average throuhput of 30683 bps, and a packet loss of 0%. The system is able to send information notifications to telegram well. Keywords: Forest Fires, Wireless Sensor Network, MQTT, and Sensor Node